Облік в системі забезпечення інформаційних потреб користувачів при управлінні підприємством - Голуб, Наталя Олександрівна; Голуб, Наталья Александровна; Holub, Natalia (Луцький національний технічний університет, 2016)
UK: У статті розглянуто облікове забезпечення управління діяльністю підприємств, функціонування системи бухгалтерського обліку інформаційним запитам користувачів облікової інформації та розглянуті пропозиції по удосконаленню інформаційного забезпечення. EN: The article highlights the economic substance of accounting information in enterprise management and accounting in the management system. Important is the use of accounting information. The management accounting function was constantly deepened and improved. To check information added control and analytical. Accounting has become an objective necessity of modern method of production, of its management. Moreover, under the influence of changes in the activity of enterprises – the management complexity, improve production technology and introduces new features. It is determined that account information is not only key to the successful adoption of timely and effective management decisions, and allows you to solve urgent problems in the field of economy, a balanced use of resources, social protection of employees. Reviewed account management activities, where it is found that accounting is a unified information system, the purpose of which is to provide information management processes for the effective use of resources and the preservation of property. Investigated the functioning of the accounting system information needs of users of accounting information and determined that to ensure the information needs of different users of accounting should consist of subsystems, namely financial, managerial and tax accounting. In the basis of accounting imposed requirements that are put forward to it by various users of accounting information. Scope of accounting — enterprises, organizations, institutions, industrial, commercial, banking and other spheres of activity, and through summarizing of accounting data and reporting — industry, economy (economy) of individual countries, the world economy as a whole. Analyzes the current information provision of accounting information according to users ' requirement. So, well-established accounting provides timely management needs sufficient and reliable information to implement and support appropriate management decisions according to the requirements of public relations and gives you the ability to use data to improve the condition of any entity (economy) of the market in time and space. Identified positive aspects about the proposals to improve information security.
The accounting system ensuring the information needs of the management of the enterprise
Keywords: користувачі; інформаційне забезпечення; облік; інформація; інформаційна потреба; users; information support; accounting; information; information need